Financial viability of a fully simulated transformation from even-aged to uneven-aged stand structure in forests of different ages. (2nd March 2021) - Vítková, Lucie; Saladin, Dominik; Hanewinkel, Marc
Abstract: For the first time, an economic analysis of a fully simulated forest transformation process from even-aged to uneven-aged stand structure using natural regeneration was performed using an individual tree growth simulator. A comparison to a 'business as usual' management approach (i.e. age-class scenario) was also made. Norway spruce ( Picea abies (L.) Karst.)-dominated forests of different ages were selected for the simulation: forest at thinning stage (52 years; hereafter, 'younger stand') and a mature stand (95 years) to explore different starting points for the transformation. The harvested and remaining stand volume showed only little fluctuation over the course of the simulation period in the case of the transformation (uneven-aged) scenario. The age-class scenario, on the other hand, showed peaks and drops in the timber volume. The land expectation values at the end of transformation were higher ( i  = 1 or 2 per cent) or equal ( i  = 3 per cent) to those of the age-class scenario for the younger stand. The transformation of younger forests appears to be economically interesting (under interest rates above 2 per cent) as the early revenues of more intensive thinnings achieve an equilibrium growing stock well below the potential maximum growing stock of an even-aged stand. This suggests transformation management to be economically efficient under the given silvicultural and economic conditions. The transformation of mature stands was found to be less economically viable due to the lower holding values for the transformation (uneven-aged) scenario compared with the age-class scenario. However, the holding values of the younger stand were higher for all interest rates compared with the age-class scenario. This study concludes that transformation (uneven-aged) scenario yielded more economically viable silvicultural approach (in the case of younger forests) and a steadier trend in harvested and remaining timber volume showing no major fluctuations. Transformation approach also forms a better foundation where other ecosystem services can be built.